Evaluation of Serodiagnostic Assays for Mycobacterium bovis Infection in Elk, White-Tailed Deer, and Reindeer in the United States. (25th June 2012) - Nelson, Jeffrey T.; Orloski, Kathleen A.; Lloyd, Audra L.; Camacho, Mark; Schoenbaum, Mark A.; Robbe-Austerman, Suelee; Thomsen, Bruce V.; Hall, S. Mark
Abstract : In 2011, the United States Department of Agriculture conducted a project in which elk ( Cervus elaphus spp.), white-tailed deer (WTD) ( Odocoileus virginianus ), and reindeer ( Rangifer tarandus ) were evaluated by the single cervical tuberculin test (SCT), comparative cervical tuberculin test (CCT), and serologic tests. The rapid antibody detection tests evaluated were the CervidTB Stat-Pak (Stat-Pak), and the Dual Path Platform VetTB (DPP). Blood was collected from presumably uninfected animals prior to tuberculin injection for the SCT. A total of 1, 783 animals were enrolled in the project. Of these, 1, 752 (98.3%) were classified as presumably uninfected, based on originating from a captive cervid herd with no history of exposure to TB. Stat-Pak specificity estimates were 92.4% in reindeer, 96.7% in WTD, and 98.3% in elk and were not significantly different from SCT specificity estimates. Using the DPP in series on Stat-Pak antibody-positive samples improved specificity in the three species. Thirty one animals were classified as confirmed infected, based on necropsy and laboratory results, and 27/31 were antibody positive on Stat-Pak for an estimated sensitivity of 87.1%. The study findings indicate that rapid serologic tests used in series are comparable to the SCT and CCT and may have a greater ability to detect TB-infected cervids.